2002
DOI: 10.1046/j.1471-4159.2002.00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in metabolism and gene expression in brain regions during cuprizone‐induced demyelination and remyelination

Abstract: Exposure of mice to the copper chelator, cuprizone, results in CNS demyelination. There is remyelination after removal of the metabolic insult. We present brain regional studies identifying corpus callosum as particularly severely affected; 65% of cerebroside is lost after 6 weeks of exposure. We examined recovery of cerebroside and ability to synthesize cerebroside and cholesterol following removal of the toxicant. The temporal pattern for concentration of myelin basic protein resembled that of cerebroside. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
84
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 50 publications
9
84
0
Order By: Relevance
“…Several studies have applied microarray analysis to investigate gene expression changes associated with de-myelination and remyelination (Arnett et al, 2003;Jurevics et al, 2002;Morell et al, 1998). These studies were, however, to a certain extent tainted by the use of whole tissue lysates.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have applied microarray analysis to investigate gene expression changes associated with de-myelination and remyelination (Arnett et al, 2003;Jurevics et al, 2002;Morell et al, 1998). These studies were, however, to a certain extent tainted by the use of whole tissue lysates.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the chelation of copper causes demyelination and an upregulation of IGF-1. 43 Vitamin B12 deficiency 44 and chronic nitrous oxide exposure, 45 both of which impair MS, also cause demyelination. We found that Cu 2 þ promotes MS activity (Table 1) and protects against the inhibitory effects of other metals (Figure 5e), while Cu 2 þ chelation has an opposite effect (Figures 5a and f).…”
Section: Igf-1 and Dopamine Regulate Methionine Synthase M Waly Et Almentioning
confidence: 99%
“…An alternative to genetic screening is to use recently developed gene profiling methods. Previous gene profiling studies of OPCs and OLs have focused on either the process of demyelination versus remyelination in CNS tissue derived from cuprizonedemyelinated animals (Jurevics et al, 2002;Arnett et al, 2003), or on the differences between uncommitted neural precursors and OPCs (Hu et al, 2004), as opposed to the terminal differentiation step of primary OPCs into mature OLs.…”
Section: Introductionmentioning
confidence: 99%